EFEKTIVITAS PELAKSANAAN E-PROCUREMENT DALAM PENGADAAN BARANG DAN JASA - Muhammad Mujtaba Habibi; Sri Untari (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2018)
This study aims to analyze the effectiveness of the implementation of E-procurement in the procurement of goods and services in the city government of Malang, and analyze the obstacles in its implementation. The research method used is descriptive qualitative. Data collection techniques are done by documentation observation and interview. Data analysis uses an interactive model. The results of the study showed that in general the implementation of e-procurement in the procurement of goods and services in the City Government of Malang effectively as evidenced by the implementation of a transparent and accountable tender so that it was possible for each company to take part in the tender. The obstacles in implementing e-procurement are the existence of dual positions, unsatisfactory human resources and unsupportive infrastructure